Adaptações morfofisiológicas de araucária ao sombreamento - Sasso, Simone Aparecida Zolet (2019)
To verify the morphophysiological adaptations of the arauca ria under shading, two experiments were carried out, one in agroforestry environment with two sizes of seedlings and another under controlled shade. In the agr oforestry experiment 124 large a raucaria seedlings were planted: 35 45 cm; and small: 15 25 cm in height, and submitted to two conditions of luminosity: in f ull sun and shading in agroforest. The seedlings were evaluated 18 months after planting for survival, growth, gas exchange, photosynthetic pigments and foliar anatomy. After 23 months of planting the canopy of the agroforestry was parti ally opened and the arauca rias were reassessed at 25 months of planting . In controlled shade the arauca ria seedlings were cultivated for 21 months at four levels of shade: 0% (full sun), 30%, 50% and 80% of total solar radiation. Growth analyzes, photosynthetic pigments, and chlorophyll a fluorescence were performed. The plants under shading were exposed to full sun for a period of 24 hours and the chlorophyll a fluorescence was evaluated. In the agroforestry the seedlings planted in full sun had greater survival, growth, amo unt of pigments and greater photosynthesis, in relation to the shaded seedlings, at 18 months of planting. Large seedlings had greater survival and growth compared to small ones in full sun. Shaded a rauca ria leaves were smaller, less thick and with reduced differentiation of palindromic parenchyma and hypodermis. After opening the canopy there was a rapid resumptio n of the growth of shaded arauca rias, due to the increase of photosynthesis. In the environment with controlled shading, it was observed that in the higher incident radiation the plants presented larger diameter, higher total dry mass, greater root dry mass distribution, higher D ikson quality index, high pigment contents and high transport rate of electrons, demonstrating the highest quality of see dlings under higher radiation. When the shaded plants were exposed to full sun for a period of 24 hours, they significantly increased the rate of electron transport. Under shading the plants showed adaptations, which would be the increase in the amount of chlorophyll and the greater quantum efficiency of photosystem II. These results indicate that the species tolerates strong shading and has high efficiency in the capture and use of light, as it responds quickly when there is gre ater light in the canopy. Ar auca ria seedlings of large size and high light exposure are recommended in intercropping plantations.